Integrated STEM Teacher’s Guide in Mathematics 2 (Ascendens Asia Singapore – Union Christian College Philippines Journal of Multidisciplinary Research Abstracts, 2020)
In today's fast and changing world, it is of crucial importance that children get the optimum learning from school, which will help them gain the necessary ability and skills needed in this competitive globalized world. It is due to this that schools give interventions to meet quality education. This study was conducted to look into the effectiveness of the integration of Science, Technology, and Engineering in teaching Mathematics as an intervention on the Mathematics performance of the Grade 2 pupils. The respondents of the survey were the 32 Grade 2 learners of Ilocanos Elementary School, City of San Fernando, La Union during the School Year 2019-2020. This study employed the quasi-experimental design. Mean scores and Wilcoxon signed-rank were utilized to analyze and interpret the data gathered. The result showed that the respondents gained improvement from pre-test to post-test. The regular implementation of the integration of science, technology, and engineering concepts in teaching Mathematics determined the changes in their performance since there was a substantial difference in the pupils’ performance before and after the intervention. It is concluded that the Integrative STEM Module proved to be a relevant and helpful tool for improving the Mathematics skills and performance of pupils. Hence, the Integrative STEM Module in Mathematics is strongly recommended for adoption.
Keywords: STEM, integrative teacher’s guide, Grade 2 Mathematics